Flare-up of pustular psoriasis after ustekinumab therapy: Case report and literature review - Ying-Xiu Dai; Chih-Chiang Chen (Wolters Kluwer Medknow Publications, 2018)
While tumor necrosis factor-alpha (TNF-α) inhibitor has been shown to be paradoxically associated with the development of psoriasis, there are few reported cases of pustular psoriasis potentially induced by ustekinumab in the literature. Here we present the case of a 70-year-old male with chronic plaque psoriasis who experienced pustular psoriasis nine days after initiating ustekinumab therapy. The pustular lesions resolved after acitretin treatment, and he restarted ustekinumab 45 mg at week 4, and every 12 weeks thereafter. No recurrence of pustular psoriasis occurred during the 6-month follow-up. Our case suggested that ustekinumab-induced pustular psoriasis can be successfully managed with acitretin while maintaining ustekinumab therapy as well. Keywords: Adverse events, Flare, Pustular psoriasis, Ustekinumab